PALAEOSEISMOLOGICAL ANALYSIS OF THE EAST GIOUCHTAS FAULT, HERAKLION BASIN, CRETE (PRELIMENARY RESULTS) - Zygouri, V.; Koukouvelas, I.; Ganas, A. (Bulletin of the Geological Society of Greece, 2016)
A paleoseismological analysis has been performed at the East Giouchtas Fault. This fault dips to the east and represents a pure normal fault. The East Giouchtas Fault forms an intrabasinal high in the Heraklion basin with its conjugate fault the West Giouchtas Fault. A natural surface has been prepared and logged in detail in order to detect the most significant parameters related to the ground shaking impact on the area. Investigating past earthquakes characteristics attributed to the East Giouchtas Fault and through sample dating we conclude that the studied fault is related to at least four strong events of 6.4 magnitude. The fault is also characterized by 20-40 cm tectonosedimentatry displacements and slip rates of 0.25 mm/yr. Thus, the proximity of the fault to the highly populated Heraklion city and Minoan Knossos monument urges the need for an adequate hazard assessment of the area.